Pengaruh Outdoor Learning Terhadap Sikap Siswa Pada Mata Pelajaran Matematika - Prima Crismono (Universitas Islam Jember, 2023)
A teacher is expected to use a modified learning method. One method that can be modified is the outdoor learning method. The purpose of this research was to determine the effect of outdoor learning on students' attitudes toward mathematics. This type of research is comparative research with a quantitative approach. The method used in data collection is the questionnaire method. The data analysis method uses the Wilcoxon signed-rank test. From the results of the data analysis, it can be concluded that the calculated Z value obtained is -5.514 (the price is not considered because the price is absolute) and because this statistical value is greater than the significance level (α) = 0.05 so it can be concluded that the Outdoor Learning learning method has a significant influence on students' attitudes from disliking to liking mathematics. It can be concluded that in this study the Outdoor Learning method has a significant effect on changing the attitude students dislike towards the subject of mathematics. Keywords: outdoor learning and student attitude